Effect of sorafenib on sperm count and sperm motility in male Swiss albino mice - Surekha Devadasa Shetty; Laxminarayana Kurady Bairy (Wolters Kluwer Medknow Publications, 2015)
The issue of male germ line mutagenesis and the effects on developmental defects in the next generation has become increasingly high profile over recent years. Mutagenic substance affects germinal cells in the testis. Since the cells are undergoing different phases of cell division and maturation, it is an ideal system to study the effect of chemotherapeutic agents. There are lacunae in the literature on the effect of sorafenib on gonadal function. With background, a study was planned to evaluate the effects of sorafenib on sperm count and sperm motility in male Swiss albino mice. Male Swiss albino mice were used for the study. The animals were segregated into control, positive control (PC) and three treatment groups. PC received oral imatinib (100 mg/kg body weight) and treatment groups received 25, 50, and 100 mg/kg body weight of sorafenib orally for 7 consecutive days at intervals of 24 h between two administrations. The control group remained in the home cage for an equal duration of time to match their corresponding treatment groups. The animals were sacrificed at the end of 1 st , 2 nd , 4 th , 5 th , 7 th , and 10 th weeks after the last exposure to drug, respectively. Sperm suspensions were prepared and introduced into a counting chamber. Total sperm count and motility were recorded. There was a significant decrease in sperm count and sperm motility by sorafenib which was comparable with the effect of PC imatinib. Sorafenib adversely affects sperm count and sperm motility which are reversible after discontinuation of treatment.